(untitled) (Research, Society and Development, 2022)
The present work brings a reflection on how care and health care was built for the homeless population in Brazil. It is a population surrounded by stigmas and lacking everything, for this reason this construction took place slowly and began with a strong welfare character. With the reformulation of the National Primary Care Policy, a specific model of care was instituted for the care of this population, the Consultório na Rua (CnaR), in which the teams provide care in circumstances different from those they are used to. The numerous difficulties inherent to this process are highlighted, such as the difficulty of intersectionality and the bureaucratic barriers that prevent their access to continuous care. It is concluded that the professional who works in the CnaR team needs to understand the health-disease process of these people and practice a qualified listening, with an ethical positioning, in addition, they must break the barrier of standardization to offer a humanized, singularized, qualified care, with a sensitive listening, capable of welcoming the user and his demands.